Stress Management in Pre- and Postoperative Care Amongst Practitioners and Patients in Cardiac Catheterization Laboratory: A Study Protocol - Block, Andrea; Bonaventura, Klaus; Grahn, Patricia; Bestgen, Felix; Wippert, Pia-Maria (Frontiers in Cardiovascular Medicine, 2022)
Cardiac catheterization examination is challenging for both patients and practitioners. Several potential stressors can occur during the procedure. The objective of the study is to implement stress-management interventions for practitioners and patients that aims to reduce the psychological and physical strain of a cardiac catheterization. The randomized, controlled study includes two intervention trails with parallel groups, for patients with elective cardiac catheterization and practitioners at the catheterization lab at two hospital sites. The patient intervention comprises a psychoeducational video and a standardized medical information. The control condition includes the usual medical patient education. Primary and secondary outcomes are measured by physiological parameters and validated questionnaires, the day before (M1) and after (M2) the intervention and at a six-months follow-up (M3). It is expected that patients of the intervention group show reduced complications and medication, better pre- and post-operative well-being, and lower stress levels. The intervention for practitioners includes a Mindfulness-based stress reduction program over eight weeks (supervised directly at the clinic site and home-based) and an operative guideline. It is expected that practitioners of the intervention group show improved perceived and chronic stress, better sleep and regeneration, higher effort-reward balance, and quality of life. Primary and secondary outcomes are measured by physiological parameters (heart rate variability, salvia cortisol) and validated questionnaires before (M1) and after (M2) the MBSR intervention and at a follow-up six months later (M3). Physiological biomarkers will be assessed pre- (M1) and post intervention (M2) on a work day and a day off. Intervention effects in both groups will be evaluated separately using multivariate variance analysis. This study evaluates the effectiveness of two stress-management intervention programs for patients and practitioners within cardiac catheter laboratory. For patients, the intervention may reduce complications and sedative medication, perceived stress and improve post-operative well-being. For practitioners, it may contribute to improved perceived and chronic stress, working conditions and well-being. The study may add knowledge how to eliminate stressful exposures and to contribute to more (psychological) security, less output losses and exhaustion during work. The evolved stress management guidelines, training manuals and the standardized patient education will be transferred into clinical routines.